Discharge Modes Suggested by Emission Spectra of Nitrogen Dielectric Barrier Discharge with Wire-Cylinder Electrodes - 杨富翔 牟宗信 张家良 (Plasma science & technology, 2016)
In this paper,nitrogen dielectric barrier discharge（DBD） plasma was generated in a quartz tube with coaxial wire-cylinder electrodes at atmospheric pressure.By varying the nitrogen gas flow（FN） in the range of 0-1 m3/h,the plasma optical emission spectra（OES） were measured and studied.The vibration（T_（vib）） and rotation temperature（T_（rot）） of nitrogen were obtained,by fitting the rovibronic bands of N_2（C~3∏_u-B~3∏_g,0-1）,and by the Boltzmann plot method for purposes of comparison.T_（vib） increased up to 2481 K with increasing nitrogen flow till0.2 m3/h,and then decreased with further increasing FN,while Trot decreased monotonously and approached to-350 K for FN ≥ 0.6 m~3/h.The intensity of N_2（C~3∏_u-B~3∏_g,0-0,1-0,0-3） and N_2~＋（B~2∑_u~＋-X~2Σ_g~＋,0-0） exhibited similar evolution with increasing FN to those of the T_（vib） and Trot,respectively.The discharge photos revealed that the discharge filaments gradually decreased with increasing FN,and eventually disappeared,which implied that a discharge mode transition emerged with increasing FN.The possible mechanism for the discharge mode transition is studied in detail according to the vibration（T_（vib）） and rotation temperature（T_（rot）） of nitrogen.